Innovativeness and Firm Performance of Kuala Lumpur SMEs : The Moderating Role of Information Technology Capability - Looi, Wen Hao (Universiti Malaysia Sarawak (UNIMAS), 2015)
This research was conducted to investigate the relationship between five underlying dimensions of innovativeness and firm performance with the information technology capability as moderator. Questionnaires were distributed to 102 executives or managers ranging from small to medium sized firms throughout Kuala Lumpur. Data collection is done through the convenient sampling method. Based on this study, the results indicated that only one dimension of innovativeness which is market turbulence is significantly and negatively related to firm performance. The other four dimensions of innovativeness was founded have no significant relationship with firm performance. Last but not least, the results also revealed that information technology capability do not moderate the relationship between innovativeness and firm performance but these factors however have direct positive impacts on firm performance.